THE IMPORTANCE OF READING - Pulatova Mukhlisa Dilshod qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. This article discusses the importance of reading in human life, its impact on thinking, knowledge and the spiritual world. Books enrich a person with new knowledge, broaden his worldview and develop his thinking skills. The impact of reading on personal and professional development is also discussed.